DTM generation from LiDAR data by using different filters in open-source software - Sulaiman, Nurul Shahida (Faculty of Geoinformation Science & Engineering, Universiti Teknologi Malaysia, 2010)
The goal of this study is to analyze the suitability of filtering method in Open-Source (OS) software towards the generation of Digital Terrain Model (DTM) by using Light Detection and Ranging (LiDAR) data. DTM is a digital representation of ground surface topography. It can be generated by filtering process of point clouds using either OS software or commercial software. OS software is computer software which allows user to freely download it via internet. By taking Ayer Hitam, Penang as a research area, LiDAR data of that area is processed using LiDAR OS software which is Airborne LiDAR Data Processing and Analysis Tools (ALDPAT). Five different filters in ALDPAT are used respectively to filter the same LiDAR data. In addition, commercial software, TerraScan is then used to process the same data since this software has the capability to produce high quality DTM and it is commonly used by the Department of Surveying and Mapping Malaysia (DSMM). The quality of DTMs generated by ALDPAT is evaluated by comparing them to the DTM gained by TerraScan. Two approaches are used; first, detecting differences and eliminating the results which contained obvious differences. Secondly, 3-dimensional (3D) - Deviation method is used upon the result which the differences cannot be easily detected. Elevation Threshold with Expand Window (ETEW) filter has produced almost similar DTM as the one produced by TerraScan with 47mm standard deviation.